The peculiarities of attitude formation to foreign products - Paukštė, Vaidotas; Normantas, Mantas; Normantienė, Lina (Business, Management and Economics Engineering, 2010)
Nowadays the attitude formation is one of the most popular topics in marketing literature. However, in the scientific literature there are many publications, which exclude different factors. Despite this fact, in scientific literature there are not a lot of publications about attitude formation to foreign products. In this publication scientific literature analysis of attitude, attitude formation and ethnocentrism is accomplished. This publication discloses the main attributes of attitude formation to foreign products. According to the results, the customers‘ experience has the biggest influence on attitudes to foreign products. Also, it was found, that other attitude formation factors have an influence on attitude, but the influence is small when customers are ethnocentric.Article in Lithuanian.Požiūrio į užsienio produktus formavimo ypatumai